Active Disturbance Rejection Power Predictive Control of Rectifier Based on Bus Voltage Optimized ESO Observer - Xiong Xiao; Junyu Zhao; Xian Song; Yuntao Zhao; Yongjun Zhang; Fei Zhang (IEEE Access)
In the control system of three-phase voltage source pulse width modulation rectifier, dynamic control of direct current bus voltage has become the research focus. This paper proposes an active disturbance rejection control- model predictive direct power control strategy, without a bus voltage sensor, aiming at improving the fault tolerance of the direct current side. This strategy considers the dynamic response ability of rectifier operation without a voltage sensor and avoids the outer loop feedback distortion caused by voltage sensor faults. Model predictive direct power control is used in the inner loop. For the improvement of system response performance, bus voltage extended state observer and active disturbance rejection controller are designed for the outer loop. In addition, error differential term is added to the extended state observer to realize fast tracking of dynamic voltage without sensor. An adaptive threshold is designed by comparing the residual error and threshold, which realizes the fast switching and system normal operation under voltage sensor fault. The proposed control strategy is verified by simulation and experiment. The results show that the observation error of the proposed strategy is within 2 V, which is down about 2 V from direct power control and model predictive direct power control. When the bus voltage step, the observed voltage fluctuation is 5 V, and the adjustment time is about 75 ms. Combined with the strategy, extended state observer can well track the dynamic change of bus voltage and realizes automatic switching control under sensor fault.